Whales and whaling. (Australia Government Publishing Service, 1978)
Contents : v.1 : Report of the Independent Inquiry conducted by The Hon. Sir Sydney Frost; v.2 : Papers commissioned by the Inquiry conducted by the Hon. Sir Sydney Frost